The Outlook of Financial Consumer Protection in China: Learning from the American Approach - Wang, Jiawen; Wang, Qianqian (Technium Social Sciences Journal, 2024)
In China, the range of financial derivative products has expanded considerably in recent years, with a corresponding increase in the complexity of these instruments. Financial institutions now offer a diverse array of financial products to consumers. There is a considerable disparity between financial consumers and financial institutions in a number of areas, including economic strength, social status, professional composition, negotiation ability and even judicial resources. Consequently, the topic of financial consumer protection is receiving increasing attention, and this issue is also a matter of considerable concern to countries around the world. A unified and effective system for the protection of financial consumers has yet to be established in China. In the event of a dispute regarding the consumption of financial products, it is often challenging for consumers to pursue appropriate redress, resulting in a situation where they have no recourse. The question of whether China should enact a unified Financial Consumer Protection Law, establish an independent financial consumer protection agency, and integrate the measures and regulations for protecting financial consumers in the financial services market in order to provide a convenient and fair mechanism for handling financial consumption disputes is a key area of study.